Ultrasonic waves for materials evaluation in fatigue, thermal and corrosion damage: A review. (1st April 2019) - Marcantonio, Vera; Monarca, Danilo; Colantoni, Andrea; Cecchini, Massimo
Highlights: This is a review paper on non-linear ultrasonic techniques for damage evaluation. Fatigue, thermal and corrosion damage was considered. Principles, advantages and disadvantages of different measurement method are covered. Remaining gaps and future challenges are discussed. Abstract: Mechanical properties of materials tend to deteriorate over time and thus become responsible for cracks and malfunctions in mechanical components or civil structures. Non-destructive ultrasonic wave analysis has proven to be a successful investigation method for inspecting mechanical properties of materials. This review has highlighted the main results of research in the field of non-linear ultrasonic wave investigations for the inspection of fatigue damage, thermal damage and chemical damage. In all three cases, non-linear ultrasonic wave survey method was effective in detecting first-stage damage.